Study of the diffusion coefficients of diphenylbutadiene and triclosan into and within meat - Silva, A. Sanches (2011)
The migration of two chemicals, diphenylbutadiene and triclosan, was the target of this paper. Pork meat with different fat contents was prepared to study the influence of this parameter in the migration levels and to study the rate of diffusion of these migrants into the whole plastic/foodstuffs system and within the foodstuff. The whole system plastic/foodstuff diffusion coefficient (effective D) was calculated according to an equation based on the Fick’s Second Law, and D within the foodstuff (DF) was calculated according to the Moisan equation. At 5 C, DF was 1.6 9 10-7 and 1.7 9 10-7 cm2/s for DPBD and triclosan, respectively. At 25 C, DF was 3.7 9 10-7 and 3.9 9 10-7 cm2/s for DPBD and triclosan, respectively. As expected, D within the pork meat is faster than the whole system D, which means that the interface plastic/foodstuff may be the limiting step for the mass transport of chemicals from the packaging to the foodstuff.